Perlindungan Hutan Ulayat Masyarakat Hukum Adat Sawai dari Kegiatan Usaha Pertambangan - Olvin Hady (Jurnal Cakrawala Hukum, 2018)
This research is aimed to understand and analysis about the incompatibility of national law in the rejection from customary law community of sawai in order to protect the ulayat forest from the mining business activities of PT.WBN. Also this research aimed to give a solution about how to solve the conflict between customary law community of sawai with PT. WBN as a form of legal protection. The type of this research is empirical juridical with juridical sociology approach. The procedure to collect the data is use library research as the technique to analysis and also used the technique analysis of legal material with descriptive qualitative as the method. The result of this research is to show The resistance of law community of sawai is contrary with national law. The right forest is the forest area of customary law community.  The Settlement of the conflict from PT.WBN with customary law community not already find a solution to solve the problem. It is because there is a differences between the price of land acquisition which is unappropriated with the demand of customary law community of sawai. And also there is tendencies from the district government of Halmahera Tengah which is more partiality with PT.WBN.How to cite item: Hady, O. (2018). Perlindungan Hutan Ulayat Masyarakat Hukum Adat Sawai dari Kegiatan Usaha Pertambangan. Jurnal Cakrawala Hukum, 9(1), 68-78. doi:https://doi.org/10.26905/idjch.v9i1.2113